2007
DOI: 10.1042/ba20060105
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietic and anti‐obesity effects of Garcinia cambogia (bitter kola) in Wistar rats

Abstract: The anti-obesity and erythropoietic effects of crude ethanolic extracts of Garcinia cambogia (bitter kola) seeds on Wistar rats (Rattus norvegicus) were investigated. The rats were divided into three dosage groups: A (0 mg/kg of body weight), B (200 mg/kg) and C (400 mg/kg). Weight changes, plasma lipoprotein levels and the lipid profile of the liver, gastrointestinal system and adipose tissue were monitored as indices for anti-obesity, while the RBC (red blood cell) count (assessed by using a haemocytometer) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…enhance fertility either directly or indirectly and that most plants rich in antioxidants have the tendency to increase sperm count, motility, and enhance sperm morphology Adesanya et al, 2007). The African catfish C. gariepinus is a major cultivated fish of high commercial value in Nigeria and is ideal for captive breeding (Adesulu & Syndeham 2007) but many limitations are associated with fry production and the development of better broodstock management techniques is crucial for improvement of fry yield and system efficiency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…enhance fertility either directly or indirectly and that most plants rich in antioxidants have the tendency to increase sperm count, motility, and enhance sperm morphology Adesanya et al, 2007). The African catfish C. gariepinus is a major cultivated fish of high commercial value in Nigeria and is ideal for captive breeding (Adesulu & Syndeham 2007) but many limitations are associated with fry production and the development of better broodstock management techniques is crucial for improvement of fry yield and system efficiency.…”
mentioning
confidence: 99%
“…The ever-growing demand for the seed of African catfish C. gariepinus calls for more production of high quality milt which could be used to fertilize the eggs in the hatchery. It has been shown by several studies that medicinal plants can influence fertility in man, animal and fish (Oluyemi et al, 2007;Salman et al, 2008;Dada, 2012). According to Bahmanpour et al, (2006), the oral administration of date palm fruit suspension doses at 120 and 240mg/kg improved sperm count, motility, morphology and DNA quality with a concomitant increase in weights of testes and Epididymis.…”
mentioning
confidence: 99%
“…17 Due to the role of citrate lyase in fatty acid biosynthesis, inhibition of this enzyme would be expected to block the synthesis and storage of triacylglycerols and result in fatty acid mobilisation from the adipose tissue.Several studies have reported this effect in rat models. 18 However, similar trends have not been reported for human trials. 13,15 Despite the current interest in the therapeutic potential of G. cambogia, scientific research is focussed almost entirely on its potential antiobesity potential.…”
Section: Introductionmentioning
confidence: 62%
“…8 Moreover, the same extracts also showed erythropoetic activity in Wistar rats. 36 Hence, additional studies are needed to assess the DNA damage and repair pathways associated with HCA exposure at high concentrations. Moreover, our results ascertain the safe consumption of HCA within the acceptable dose limit (∼2800 mg/day).…”
Section: Ghosh I Et Al: Cyto-genotoxicity Of Hydroxycitric Acid In Vmentioning
confidence: 99%